The Voice of English Language Study Program Students towards Online Debate Learning during Pandemic Covid 19 - Latief, Dewi Sasmita; Basalama, Nonny; Mohammad, Titien Fatmawaty (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
This research aims to find out the voice of ED students towards the effectiveness of online debate learning during pandemic Covid-19. This research use quantitative approach, and collects the data by questionnaire instruments trough Google Form. It took 32 participants of fourth semester in academic year 2020/2021. The result of this research revealed that percentage of students perception that used Likert Scale scoring and processed by using Formula of Sugiyono, the percentage is 63,74% which accumulated from the percentages of perception indicators that is Acceptance or Absorption is 61,32%, Understanding or Comprehending is 63,82%, and Evaluation or Assessment is 66,09%. This percentage is the good category that according to Sugiyono's classification which mentioned that 61-80% is classified as good perception. Even though, 63,74% is the low standard of perception score. This low average of perception caused by the students' negative perception that is complained about technical obstacles such as unstable internet connection, out of mobile quota, and also the limited internal storage. Furthermore, in open-question in the last part of questionnaire, there are only 2 students who have positive perception, 14 students have negative perception while 12 students have both positive and negative perception. From the result of all data process, I concluded that the students were perceived that this online learning is effective in replacing offline learning during pandemic Covid-19. However, the students preferred offline class in practicing debate skill. As the consequence, this research recommended the teacher and the students to always have a plan B in solving these obstacles during online debate amid pandemic Covid-19. In addition, this research still needs further study that can resolve their difficulties properly.